Finding a Place for Father: Selling the Barbecue in Postwar Canada - Dummitt, Chris (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractBetween the late 1940s and the mid 1950s, a group of advertisers, cookbook writers, and pop culture journalists introduced Canadians to a new form of household cookery: the barbecue. While grilling food over a fire was not entirely new, the cultural form and meaning of postwar suburban barbecuing sprung directly from middle-class family life and gender relations in 1950s Canada. In particular, this paper explores why men played such a key role in outdoor cooking and how sellers of barbecue culture attempted to normalise this apparent transgression of 1950s gender expectations. It argues that barbecuing was one of a number of postwar male-centred family leisure activities that resulted from changing notions of fatherhood-namely, an increased expectation that men be more involved in domestic life. This study of postwar barbecue culture shows that when gendered divisions between public and private faltered, new divisions between leisure and work took their place, re-articulating and redefining existing hierarchies between masculine and feminine.